Evaluation of curved root canals filled with a new bioceramic sealer: A microcomputed tomographic study using images with different voxel sizes and segmentation methods - Pinto, Jader Camilo [UNESP]; Torres, Fernanda Ferrari Esteves [UNESP]; Lucas-Oliveira, Everton; Bonagamba, Tito Jose; Guerreiro-Tanomaru, Juliane Maria [UNESP]; Tanomaru-Filho, Mario [UNESP] (Wiley, 2021)
The aim of this study was to investigate the filling ability of a new premixed bioceramic sealer in comparison with an epoxy resin-based sealer in curved root canals using different segmentation methods and voxel sizes in micro-CT images. Twelve curved mesial roots of mandibular molars with two separated canals were selected. All root canals were prepared by using HyFlex EDM files size 25/.08 and filled by the single cone technique and Bio-C Sealer or AH Plus (n = 12). The samples were scanned by micro-CT at 5 μm. The images were analyzed at 5, 10, and 20 μm for the volumetric analysis of voids in filling. Visual image segmentation was performed by two examiners, and the automatic segmentation was accomplished for comparison. Radiopacity of the sealers was evaluated by radiographic analysis. Data were submitted to the two-way ANOVA and non-paired t tests at a significance level of 5%. AH Plus had the highest radiopacity (p <.05). Root canals filled with AH Plus or Bio-C had similar low percentage of voids (p >.05). There was no difference interobserver, which had similar results to those obtained with automatic segmentation for all voxel sizes evaluated (p >.05). Bio-C Sealer had appropriate filling ability. Visual and automatic segmentation can be applied to micro-CT images with voxel sizes from 5 to 20 μm to evaluate the filling of sealers with adequate radiopacity. Automatic segmentation should be used as a faster method.
Keywords: calcium silicate; dental materials; physical properties; root canal filling; X-ray microtomography